The lncRNA CCAT2 rs6983267 G allele is associated with decreased susceptibility to recurrent miscarriage. Issue 11 (14th April 2019) - Che, Di; Huang, Wendong; Fang, Zhenzhen; Li, Li; Wu, Haiying; Pi, Lei; Zhou, Huazhong; Xu, Yufen; Fu, LanYan; Tan, Yaqian; Lu, Zhaoliang; Li, Qingfeng; et al.
Abstract: Genetics might play various roles in susceptibility to recurrent miscarriage, and previous studies suggest that some gene polymorphisms might be associated with abortion and breast cancer onset. Colon cancer‐associated transcript 2 ( CCAT2 ) is a novel long noncoding RNA (lncRNA) transcript that might be correlated with susceptibility to multiple cancers, including breast cancer. However, whether lncRNA CCAT2 polymorphisms are related to susceptibility to recurrent miscarriage is unclear. We genotyped two lncRNA CCAT2 polymorphisms (rs6983267 and rs3843549) in 248 patients with recurrent miscarriage and 392 controls through a TaqMan real‐time polymerase chain reaction assay, and the strength of each association was evaluated via 95% confidence intervals (CIs) and odds ratios (ORs). Our results showed that the rs6983267 G allele in lncRNA CCAT2 was associated with decreased susceptibility to recurrent miscarriage (TG vs. TT: adjusted OR = 0.603; 95% CI = 0.420–0.866; p  = 0.0062; GG/TG vs. TT: adjusted OR = 0.620; 95% CI = 0.441–0.873; p  = 0.0061). The combined analysis of the two protective polymorphisms (rs3843549 AA and rs6983267 TG/GG) revealed that individuals with two unfavorable alleles exhibited a lower risk of recurrent miscarriage than those with no or only one unfavorable allele (adjusted OR = 0.531; 95% CI = 0.382–0.739). Moreover, the decreased risk associated with the two protective alleles was most obvious in women aged less than 35 years (OR = 0.551; 95% CI = 0.378–0.8803; p  = 0.0019) and in women with two to three miscarriages (adjusted OR = 0.466; 95% CI = 0.318–0.683; p  < 0.0001). In conclusion, our study indicates that the rs6983267G allele might contribute to a decreased risk of recurrent miscarriage in the South Chinese population.